Arctic Environmental Test of Tracked and Wheeled Vehicles - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1969)
The objective of the procedures is to provide a means of evaluating the suitability of tracked and wheeled vehicles in arctic winter environmental conditions.